2009
DOI: 10.1111/j.1468-3083.2008.02799.x
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive seborrhoeic keratoses associated with erythrodermic pityriasis rubra pilaris

Abstract: Boyd AS, Neldner KH, Menter A. Erythema gyratum repens: a paraneoplastic eruption. J Am Acad Dermatol 1992; 26: 757-762. 4 Piqué E, Palacios S, Santana Z. Leukocytoclastic vasculitis presenting as an erythema gyratum repens-like eruption on a patient with systemic lupus erythematosus. J Am Acad Dermatol 2002; 47: S254-S256. 5 Jablonska S, Baszczyk M, Kozlowska A. Erythema gyratum repens-like psoriasis. Int J Dermatol 2000; 39: 695-697. 6 Breathnach SM, Wilkinson JD, Black MM. Erythema gyratum repens-like figur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…Li et al [7] reported one PRP was identified in 260 cases of erythroderma. In patients with PRP related erythroderma, transient eruptive seborrheic keratoses known to have association with inflammatory diseases have been reported [8,9]. Our patient did not have the formation of seborrheic keratoses.…”
Section: Discussionsupporting
confidence: 41%
“…Li et al [7] reported one PRP was identified in 260 cases of erythroderma. In patients with PRP related erythroderma, transient eruptive seborrheic keratoses known to have association with inflammatory diseases have been reported [8,9]. Our patient did not have the formation of seborrheic keratoses.…”
Section: Discussionsupporting
confidence: 41%
“…Resolution of the seborrheic keratoses was often achieved with treatment of the underlying condition rather than any specific treatment for the keratoses. 3,4,6 The case presented here is unique because this patient's eruption began as discrete eruptive seborrheic keratoses surrounded by a halo of erythema. The erythema progressed after the initial eruptions to later become confluent in areas, especially his torso.…”
Section: Discussionmentioning
confidence: 99%
“…Eruptive seborrheic keratoses can be a sign of internal malignancy (sign of Leser-Trelat), or associated with noncancerous conditions such as inflammatory dermatoses and drug reactions. [2][3][4][5][6][7] We present an unusual case of eruptive seborrheic keratoses associated with adalimumab (Humira) use, which to our knowledge, has not been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…Öte yandan, erüptif seboreik keratozların malinitesi olmayan hastalarda da görülebileceğine dikkat çekilmiştir (psödo-Leser-Trélat belirtisi) 2 . Benzer olarak eritrodermiye yol açan inflamatuvar dermatozlar (psoriazis, pitriazis rubra pilaris), ilaç reaksiyonları, gebelik ve adalimumab kullanımının da erüptif seboreik keratozlara neden olabileceği bildirilmiştir 1,[4][5][6] . Günlük dermatoloji pratiğinde çok sayıda seboreik keratozla karşılaşıldığında ani ortaya çıkma yönünden sorgulama yapılsa da, böyle bir ilişkinin çok net tanımlanmadığı durumlarda iç organ maliniteleri yönünden rutin bir inceleme yapılmamaktadır.…”
Section: Seboreik Keratozunclassified